Political Beta. (16th February 2022) - Fisman, Raymond; Knill, April; Mityakov, Sergey; Portnykh, Margarita
Abstract: Using a portfolio theory framework, we introduce the concept of "political beta" to model firm-level export diversification in response to global political risk. Our model predicts that firms are less responsive to changes in political relations with lower beta countries—those that contribute less to the firm's total political risk. We document patterns consistent with our model using disaggregated Russian firm-by-destination-country data during 2001–2011: Trade is positively correlated with political relations, though the effect is far weaker for trading partners whose political relations with Russia are relatively uncorrelated with those of other partners in a firm's export portfolio.